2001
DOI: 10.1001/archneur.58.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Regional Magnetic Resonance Imaging Lesion Burden and Cognitive Function in Multiple Sclerosis

Abstract: Multiple sclerosis lesions show a propensity for frontal and parietal white matter. Lesion burden in these areas was strongly associated with performance on tasks requiring sustained complex attention and working verbal memory. This relationship was consistent over a 4-year period, suggesting that disruption of frontoparietal subcortical networks may underlie the pattern of neuropsychological impairment seen in many patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
2
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(140 citation statements)
references
References 28 publications
8
118
2
11
Order By: Relevance
“…Multiple studies since the 1990s have investigated the association of volume and localization of T2 hyperintense or T1 hypointense lesions with cognitive function in people with MS (for a comprehensive summary of these studies, see 54 in a study over 4 years found a correlation between performance on tests of sustained attention, processing speed, and verbal memory and frontal and parietal T2 lesion volumes at baseline and year 1 and year 4. In a study over 2 years in patients with primary-progressive MS only, change in T1 hypointense lesion volume was correlated with changes in two attentional tasks.…”
Section: Focal White Matter Lesionsmentioning
confidence: 99%
“…Multiple studies since the 1990s have investigated the association of volume and localization of T2 hyperintense or T1 hypointense lesions with cognitive function in people with MS (for a comprehensive summary of these studies, see 54 in a study over 4 years found a correlation between performance on tests of sustained attention, processing speed, and verbal memory and frontal and parietal T2 lesion volumes at baseline and year 1 and year 4. In a study over 2 years in patients with primary-progressive MS only, change in T1 hypointense lesion volume was correlated with changes in two attentional tasks.…”
Section: Focal White Matter Lesionsmentioning
confidence: 99%
“…2 Prior neuroimaging studies have almost exclusively investigated such impairment by assessing discrete cognitive domains, such as information processing speed or working memory, with neuropsychological tests that have established domain specificity. Such an approach is apparent in studies that examined both brain and lesion volumetry [3][4][5][6] and WM integrity. [7][8][9][10][11] Domain-specific cognitive tests are powerful tools that can assess the impact of MS pathology on individual cognitive domains and specific neuronal pathways, but cannot investigate cognition as a multidomain entity.…”
mentioning
confidence: 99%
“…Previous quantitative lesion tracking research [2,3,8] used total lesion volume and regional lesion volume to quantify lesion growth using one or two MRI modalities. Total lesion volume disregards location information and both approaches are limited to using one imaging modality.…”
Section: Background and Related Workmentioning
confidence: 99%